MY SAY: The Nokia way out of depression - Abd Razak, Dzulkifli (2009)
Higher education is today at the cross roads, made worse by the economic downturn because of education's close links with the marketplace — providing professionally trained graduates for the workforce. Even companies with the besteducated people have not been spared. First, the vast sums of money lost by companies led by CEOs who graduated with MBAs came as a shock to many. Second, the brazenness of these CEOs in according themselves huge rewards and bonuses although their companies are ailing, shows they are applying their own set of rules. "All across the country, there are people who work hard and meet their responsibilities every day, without the benefit of government bailouts or multimilliondollar bonuses," to quote US President Barack Obama when he insisted that everyone should "play by the same rules".